CIOP database - Zeyi Wang (19846350) (2025)
The critical interface overpotential (CIOP) database. It can be used to evaluate the lithium dendrite suppression capabilities of a given electrolyte and interface. The database is produced from a throughput experiment and a regression algorithm. 10 common SEI containing elements are included and will be updated based on more experimental data later. Welcome to submit your data. Please cite the original paper: Wang, T. Wang, N. Zhang, W. Zhang, Y. Liu, and C. Wang, Interlayer Design for Halide Electrolytes in All-Solid-State Lithium Metal Batteries, Advanced Materials, 2025, 202501838.